2022
DOI: 10.1371/journal.ppat.1010023
|View full text |Cite
|
Sign up to set email alerts
|

Making genomic surveillance deliver: A lineage classification and nomenclature system to inform rabies elimination

Abstract: The availability of pathogen sequence data and use of genomic surveillance is rapidly increasing. Genomic tools and classification systems need updating to reflect this. Here, rabies virus is used as an example to showcase the potential value of updated genomic tools to enhance surveillance to better understand epidemiological dynamics and improve disease control. Previous studies have described the evolutionary history of rabies virus, however the resulting taxonomy lacks the definition necessary to identify … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 36 publications
0
37
0
Order By: Relevance
“…We successfully constructed a phylogenetic tree with all positive samples using sequencing primers ( n = 34) for groups 1 and 2. In this study, phylogenetic analysis of the N gene revealed that all sequences were grouped into the Asian clade and the SEA4 subclade ( 27 ). We performed N gene sequencing for phylogenetic analysis in this study since N gene analysis is essential for classifying the lineage ( 27 ).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…We successfully constructed a phylogenetic tree with all positive samples using sequencing primers ( n = 34) for groups 1 and 2. In this study, phylogenetic analysis of the N gene revealed that all sequences were grouped into the Asian clade and the SEA4 subclade ( 27 ). We performed N gene sequencing for phylogenetic analysis in this study since N gene analysis is essential for classifying the lineage ( 27 ).…”
Section: Discussionmentioning
confidence: 71%
“…In this study, phylogenetic analysis of the N gene revealed that all sequences were grouped into the Asian clade and the SEA4 subclade ( 27 ). We performed N gene sequencing for phylogenetic analysis in this study since N gene analysis is essential for classifying the lineage ( 27 ). The virus subclades are identical because this is a single-institute analysis using samples from one region.…”
Section: Discussionmentioning
confidence: 71%
“…((48), Fig S1), despite different methods and RABV datasets being used in their calculations. The mean per-generation substitution rate produced through the methods described could also potentially be used in the future to estimate the size of rabies outbreaks from genetic data and calculate predicted rates of RABV lineage emergence based on the classification guidelines of MADDOG (41).…”
Section: Discussionmentioning
confidence: 99%
“…The beta regression curve and prediction interval in Figure 2C was generated using the 'betareg' R package (40). RABV lineages were assigned using MADDOG (41).…”
Section: Data and Code Availabilitymentioning
confidence: 99%
“…To analyse the distribution of Cambodian lineages within a global RABV phylogeny, maximum likelihood phylogenetic inference was performed using the program IQ‐TREE v2.0.6 (Minh et al, 2020), with 1000 bootstrap replicates and the substitution model (GTR + I + Γ) selected by the IQ‐TREE's ModelFinder tool. This first phylogenetic analysis was based on all the Cambodian N genes ( n = 354) and a balanced subset of 300 N genes isolated across all continents, and was used to visualize the RABV clades and subclades of the non‐Cambodian and Cambodian sequences (Campbell et al, 2022). The discrete phylogeographic analysis used to investigate the signature of endemicity was performed with the discrete diffusion model (Lemey et al, 2009) implemented in the software package BEAST 1.10 (Suchard et al, 2018).…”
Section: Methodsmentioning
confidence: 99%